Diabetic Distress among Patients with Type II: A Descriptive Study - Mahmoud Mohammed Ahmed; Rian Mahmood Ibrahim; Nasir Muwfaq Younis (Advanced Biomedical Research)
Background: Diabetes is a complicated, long-term condition that necessitates difficult patient self-management. This self-management includes regular medication adherence, daily insulin injections for certain patients, and daily decisions about food, exercise, and blood glucose monitoring. The objective of the study was to evaluate diabetic distress in individuals with type II diabetes. Materials and Methods: A descriptive cross-sectional study was conducted from February 2024 to May 2024 in a purposive sample of 89 patients attending the outpatient clinic of the Al-Wafia Specialized Center for Diabetes and Endocrinology, a teaching hospital in Mosul. With the help of the literature, a patients’ information form containing questions was used to gather data for a questionnaire designed to assess patients’ awareness of diabetic distress. The frequencies of the study variables were shown using descriptive statistics. A Chi-square test was used to perform a bivariate analysis. Significant P values were those that were less than 0.05. SPSS, version 25, was used to perform the statistical analyses. Results: The study outcomes showed that, with a mean of 3.636, 39% of the study sample had moderate or high levels of diabetic distress. There was no correlation found between any demographic factor and diabetic distress, except for the participant age (0.190**). Conclusion: This study concluded that among the enrolled 89 diabetic patients most of them had diabetic distress. The statistical association between overall knowledge and sociodemographic variables indicated that there is no statistically significant difference between patients’ knowledge and their sociodemographic information, except with the age group.